2023
DOI: 10.3390/fermentation9110982
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fermentation Time on the Chemical and Functional Composition of Different Cocoa Clones from Southern Colombia

Paola Andrea Polanía-Hincapié,
Juan Carlos Suárez,
Héctor Eduardo Hernández
et al.

Abstract: Cocoa bean quality depends mainly on genetic material, edaphoclimatic factors and post-harvest processes such as fermentation. The impact of the fermentation process on the chemical and functional composition of different cocoa clones grown in southern Colombia was analyzed. A factorial design with repeated measures over time was used to analyze the effect of clone and fermentation time on chemical characteristics (bromatology, phenolic compounds and antioxidant activity). The bromatological characteristics sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Cocoa ( Theobroma Cacao L.) is the basic raw material to produce chocolate and other derivatives such as cocoa butter, cocoa powder and cocoa liquor (cocoa paste) [1], which has sustained part of the daily diet of people and is currently making inroads in the cosmetics, perfumery and pharmaceutical industries [2] with a requirement in the final quality of the product. Recent studies have reported that grain quality in sensory terms is affected by different factors such as the genetics of the material [3], environmental conditions [4], the state of maturity of the grain and practices in the postharvest stage [5], such as those related to fermentation and drying [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Cocoa ( Theobroma Cacao L.) is the basic raw material to produce chocolate and other derivatives such as cocoa butter, cocoa powder and cocoa liquor (cocoa paste) [1], which has sustained part of the daily diet of people and is currently making inroads in the cosmetics, perfumery and pharmaceutical industries [2] with a requirement in the final quality of the product. Recent studies have reported that grain quality in sensory terms is affected by different factors such as the genetics of the material [3], environmental conditions [4], the state of maturity of the grain and practices in the postharvest stage [5], such as those related to fermentation and drying [6,7].…”
Section: Introductionmentioning
confidence: 99%